THE POWER OF MICROFINANCE AND SOCIO-ECONOMIC TRANSFORMATION IN NAGAPATTINAM’S RURAL COMMUNITIES - Ms.S.MAGALAKSHMI, Dr.V.VIJI (South Eastern European Journal of Public Health, 2025)
Microfinance has emerged as a powerful tool for empowering rural communities and promoting sustainable livelihoods, particularly in regions where access to traditional banking services is limited. This paper explores the impact of microfinance on rural livelihoods, with a specific focus on Nagapattinam, a district in Tamil Nadu, India. The study examines how microfinance institutions (MFIs) have contributed to the economic and social well-being of rural households by providing small loans, financial services, and capacity-building opportunities to individuals who traditionally lack access to formal credit systems. The research highlights the transformative role of microfinance in supporting rural entrepreneurship, enhancing income generation, and improving living standards in Nagapattinam. It investigates the diverse ways in which microloans have been used, from supporting agricultural activities to facilitating small-scale businesses, and the significant benefits that have emerged, including increased financial independence and improved access to healthcare and education. Furthermore, the study assesses the challenges faced by microfinance programs in the region, such as high repayment rates and the sustainability of these financial initiatives. It also discusses the role of women, who are often the primary beneficiaries of microfinance, and the positive socio-economic changes observed within families and communities due to greater financial inclusion and empowerment. By examining the case of Nagapattinam, this paper underscores the critical role that microfinance plays in fostering economic resilience in rural areas. It also provides valuable insights into how microfinance can be optimized to promote sustainable livelihoods and long-term community development. The findings contribute to a broader understanding of the potential of microfinance as a tool for rural development in India and similar contexts globally.